AB0812 PAIN CATASTROPHIZING SCORE AND GAIT, TOGETHER WITH WOMAC, ARE ALTERED IN KNEE OSTEOARTHRITIC PATIENTS UNDERGOING ARTHROPLASTY SURGERY, COMPARED WITH PATIENTS FOLLOWING CONSERVATIVE TREATMENT. PRELIMINARY RESULTS FROM HOLOA PROJECT. (June 2019) - Tío, Laura; Castro, Francisco; Tassani, Simone; Martinez, Santos; Torres, Raul; Arredondo, Raquel; Gónzález-Ballester, Miguel ángel; Monllau, Joan Carles; Noailly, Jérôme; Monfort, Jordi
Abstract : Background: Osteoarthritis (OA) is a pathology that includes several disorders that produce the same symptomatology: pain, functional impotence and inflammation. It lacks therapies that act over the physiopathology of the disease, rather than over the symptoms [1]. Patients' phenotyping is essential to describe the disorders underlying the OA symptoms, and would allow applying treatments to the altered conditions, in a personalized medicine approach. Objectives: The HOLOA project aims to design a multivariate model that allows classifying knee OA patients according their characteristics in 3 areas: pain, clinical/morphological characteristics and articular defects. The present work is a preliminary study with the aim to describe the clinical and gait dynamics differences between OA patients classified by treatment: conservative (CNS) vs arthroplasty surgery (ART). Methods: Prospective study of OA patients graded 2-3 in KL scale and classify by treatment. Both groups are paired by genre, age, and BMI. The studied variables are: WOMAC index (Pain (Wp), Stiffness (Wst) and Function (Wf), Hospital Anxiety and Depression Scale (HADS), London Chest Activity of Daily Living scale, Modified Baecke Physical Activity Questionnaire, Pain Catastrophizing Score(PCS), pain threshold (according to the extended peripatelar map of Arent-Nielsen) pain sensitization at the tibia anterior surface, pain temporal summation (these 3 parameters are measured with the use of an algometer [2]), ultrasound measurement of synovial hypertrophy and effusion, and gait analysis (with Helen Hayes marker protocol. Inverse dynamic analysis was performed to compute the reaction forces and torques of the OA and control leg [3]). Multivariate analysis of variance was performed for the treatment, genre, age and BMI. Results: This study was performed with the data of the 70 patients recruited to date. They are classified as shown in Table 1 . Only treatment factor related differences are reported. ART group present significant higher values in Wst (p=0.012), Wf (p=0.018), and PCS (p=0.018), than CNS group (Figure 1 ).Differences in PCS values show interaction with BMI (p=0.007) (Figure 2 ). Regarding the joint, number of painful sites depend on treatment and BMI group (p=0.032)(Figure 3 ). Finally, gait study show no direct effect of the treatment, interactions are observed in the reaction forces and torques when comparing control vs OA leg, in ART and CNS group (p=0.004 and p=0.002, respectively) (Figure 4 ). Conclusion: Although both treatment groups present the same OA radiologic grade, ART group presents significant higher stiffness and functional disability. That may affect to the gait of these ART patients, altering the forces distribution and torques between both legs. Although no differences in knee pain in life situation (Wp) between treatment group are reported, ART group present more painful sites in the knee with pressure stimuli. Emotional component may be playing a role in the pain and illness perception, influencing the patient decision to undergo ART surgery References: [1] Grazina, R, Adv Exp Med Biol.1059111-135, 2018 [2] Pujol, Jet al, Pain. 158(9) 1831-1838, 2017. [3] R.B. Davis, Hum. Mov. Sci. 10575–587, 1991. Acknowledgement: Funds from the MICINN (HOLOA-DPI2016-80283-C2-1-R and DPI2016-80283-C2-1-R (AEI/FEDER, UE), RYC-2015-18888) and DTIC-UPF are acknowledged Disclosure of Interests: Laura Tío: None declared, Francisco Castro Speakers bureau: Lilly, Simone Tassani: None declared, Santos Martinez: None declared, Raul Torres: None declared, Raquel Arredondo: None declared, Miguel ángel Gónzález-Ballester: None declared, Joan Carles Monllau: None declared, Jérôme Noailly: None declared, Jordi Monfort Speakers bureau: Bioibérica Procare Health